Ginsenoside Rb1 Ameliorates Diabetic Arterial Stiffening via AMPK Pathway - Zhang, Xinyu; Wang, Lei; Guo, Rong; Xiao, Jie; Liu, Xiaoling; Dong, Mei; Luan, Xiaorong; Ji, Xiaoping; Lu, Huixia (Frontiers in Pharmacology, 2021)
Background and Purpose Macrovascular complication of diabetes mellitus, characterized by increased aortic stiffness, is a major cause leading to many adverse clinical outcomes. It has been reported that ginsenoside Rb1 (Rb1) can improve glucose tolerance and enhances insulin activity, as well as restore the impaired endothelial functions in animal models. The aim of this study was to explore whether Rb1 could alleviate the pathophysiological process of arterial stiffening in diabetes and its potential mechanisms. Experimental Approach Diabetes was induced in male C57BL/6 mice by administration of streptozotocin. These mice were randomly selected for treatment with Rb1 (10mg/kg to 60mg/kg, i.p.) once daily for eight weeks. Aortic stiffness was assessed using ultrasound, measurement of blood pressure and relaxant responses in the aortic rings. Mechanisms of Rb1 treatment were studied in MOVAS-1 VSMCs cultured in high-glucose medium. Key Results Rb1 improved DM-induced arterial stiffening, as well as the impaired aortic compliance and endothelium-dependent vasodilation. Rb1 ameliorated DM-induced aortic remodeling characterized by collagen deposition and elastic fibers disorder. MMP2, MMP9 and TGFβ1/Smad2/3 pathway were involved in this process. In addition, Rb1-mediated improvement of arterial stiffness was partly achieved via inhibiting oxidative stress in DM mice, involving regulating NADPH oxidase. Finally, Rb1 could blunt the inhibition effects of DM on AMPK phosphorylation. Conclusion and Implications Rb1 may represent a novel prevention strategy to alleviate collagen deposition and degradation to prevent diabetic macroangiopathy and diabetes-related complications.